The Impact of Policy-Factors and Non-Policy Factors on Private Savings in Selected ASEAN Countries - Hdithiir, Mohamad Helmi (2002)
This study analyses trends in private savings behavior of selected ASEAN countries (Indonesia, Philippines, Malaysia, Singapore and Thailand) in perioc 1971 to 1999 and reviews policy options and non-policy options that have been thought to increase domestic savings. The policy factor variables that have been used under this study are inflation (INR) and financial market developmenl (M2). The non-policy factors are economic growth (GDP) and deII!ographics factors (DEM). The error-correction mechanism model is used to establish empirical relationships between these factors and the rate of private savings. A separate examination of the coefficients and the trends in the eplanatory variables which pro>..)'policy factors and nonpolicy factors for these five ASEAN countries shows that financial development, inflation , economic growth (Growth Domestic Product) is a crucial factor that can foster private saving in ASEAN countries.